MENINGKATKAN KECERDASAN NATURALIS MENGGUNAKAN METODE OUTING CLASS PADA MATA PELAJARAN IPAS KELAS III SDN 219/IV KOTA JAMBI - Maharani, Rachma; Faizal Chan; Hendra Budiono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of the Outing Class method in enhancing the naturalist intelligence of students in the IPAS (Science and Social Studies) subject in the third grade of Elementary School. This research is a Classroom Action Research (CAR) consisting of two cycles. The data collected includes observation data through observation sheets to assess the improvement in naturalist intelligence and the implementation of the Outing Class method by both the teacher and students. The research was conducted in four stages: planning, implementation, observation, and reflection. The study took place at SDN 219/IV, Jambi City, in January 2025. The results show an improvement in naturalist intelligence, with a pre-action score of 43%. In the first cycle, it increased to 55%, and in the second cycle, it rose further to 80%, categorized as "Good". Based on the research findings, it can be concluded that naturalist intelligence in the IPAS subject for third-grade students at SDN 219/IV, Jambi City, can be improved through the implementation of the Outing Class method.